Surgical treatment of the relaxation of the anterior wall of the vagina. - Samamé Boggio, Guido (2015)
The 52.15% or whether the total 291 cases of genital prolapses operated in the last three years, in our service, was with Curtis modified technique for correction of lesions of the anterior segment of the vagina: urethrocele and cystocele.